The Life and Poetry of Sedîduddîn Mahmûd Ibn Raḳîḳa from Diyarbakır - Ahmet Aslan (Şarkiyat Mecmuası)
This article discusses life and poetry of İbn Raḳîḳa. Ibn Raḳîḳa started his scientific life as a student ofFahruddîn el-Mârdînî. He worked under the order of alMardînî and took medicine, philosophy and literature lessons from him. Ibn Raḳîḳa became a good physician. He has successfully performed eye surgeries. In addition to his career in medicine, he was also involved in literature and poetry, wrote poems and compiled books of famous physicians in recez meter. Sources providing information about Ibn Raḳîḳa showed him among the most famous physicians of his period and also noted that he was a great poet. Unfortunately, most of his works and poems have not survived to the present day. For this reason, no detailed scientific studies have been conducted on it. We have tried to shed light on İbn Raḳîḳa’s poetry based on same of the poems included in the sorces. In this study, information was given about Ibn Raḳîḳa life and the cultural environmet in which he lived. Some of his poems and Turkish translastion that have survived to this day have been written. İnformation about his literary and scientifik personality is presented. An analysis of his poems has been made and his views on these issues have been revealed. The inferences obtained from this study are given in the conclusion section.